Understanding Cosmic Temperature, Redshift, Growth Rate and Age in Stoney Scale Black Hole Cosmology (Global Journal of Science Frontier Research, 2014)
If it is true that galaxy constitutes so many stars, each star constitutes so many hydrogen atoms and light is coming from the excited electron of hydrogen atom, then considering redshift as an index of 'whole galaxy' receding may not be reasonable. Clearly speaking, the observed cosmic redshift can be reinterpreted as an index of 'cosmological' thermodynamic light emission mechanism. During cosmic evolution, at any time in the past, in hydrogen atom-emitted photon energy was always inversely proportional to the CMBR temperature. Thus past light emitted from older galaxy's excited hydrogen atom will show redshift with reference to the current laboratory data. Note that there will be no change in the energy of the emitted photon during its journey from the distant galaxy to the observer. As there is no observational or experimental evidence to Friedmann's second assumption and as 'critical density' itself represents the density of 'growing and light speed rotating black hole', the density classification scheme of Friedmann cosmology must be reviewed at fundamental level and possibly can be relinquished.
Keywords: mach’s principle; stoney mass; black hole cosmology; cosmic growth index; cosmic growth rate; hubble potential; cosmic redshift; cosmic age; halting